Istiḥsān Method and Its Relevance to Islamic Law Reform: Content Analysis of Fatwa of Majelis Ulama Indonesia on Corneal Transplant - Johari, Johari; Maghfirah, Maghfirah; Maulidizen, Ahmad; Rizapoor, Habiburrahman (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
The progress of science in the field of medicine has brought immense advantages to human existence. Nonetheless, these advancements have both positive and negative consequences for humanity. They also give rise to deliberation and disagreement, particularly concerning Islamic jurisprudence, as not all medical technological breakthroughs can be embraced without reservation in society. This study is a descriptive, analytic, and comparative literature review. The ushuliy approach is employed to examine the methodology utilized by the two organizations in determining their stance on human corneal transplants. The primary source material used in this research is the fatwa issued by Majelis Ulama Indonesia in 2009 regarding Corneal Transplants. The data for this research was collected through a documentation method, which involves gathering information from various articles and books. The collected data was then analyzed using content analysis, which involves a descriptive and scientific examination of the key messages. The findings of this study reveal that Majelis Ulama Indonesia holds the view that corneal transplants can be performed on individuals in need, with the intention of Tabarru' (acts of charity), if there are no alternative medical options available, based on the principle of Maslahah (benefit or public interest).